The Effectiveness of the Cassava Supply Chain to Support Increasing Farmers' Income in Realizing Strong Food Security in Malacca Regency - Efandri Agustian; Marisi Marisi; Lia Nurfadhilah; Midian E Sihombing (Dinasti Publisher, 2025)
Poverty remains a major issue in Indonesia, including Malacca Regency, East Nusa Tenggara (NTT), despite the region’s strong natural resource potential. Cassava is one of Malacca Regency’s key commodities with significant potential to support local economic growth, yet cassava farmers generally remain poor and require targeted intervention. This study aims to examine the cassava supply chain management (SCM) system in Malacca Regency in order to identify an ideal management model that can support economic development and community welfare. The research uses a mixed-method sequential explanatory approach (Creswell, 2014), conducted in three phases, beginning with a preliminary survey to understand the characteristics of the cassava supply chain. The findings show that the cassava supply chain involves seven main actors: farmers, collector traders, small agents, large agents, retailers, modern markets, and consumers. The SCM system has generally operated effectively, with integrated relationships and good collaboration among actors from upstream to downstream, ensuring efficient distribution to consumers. However, farmers’ profits remain limited due to the long supply chain. The cassava supply chain includes three main flows—goods, money, and information—and overall has functioned well, enabling sustainable, long-term relationships among stakeholders.